Differences in 100-m sprint performance and skeletal muscle mass between elite male and female sprinters - Abe, T.; Dankel, S. J.; Buckner, S. L.; Jessee, M. B.; Mattocks, K. T.; Mouser, J.; Bell, Z.; Loenneke, J. P. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The sex difference in 100-m sprint performance between the world`s best athletes is approximately 10%. We hypothesized that skeletal muscle mass (SM) relative to body mass may be a major factor contributing to this difference. The aim of this study was to examine the sex difference in absolute and relative SM and sprint performance in male and female sprinters. METHODS: We analyzed the SM of male (N.=37) and female (N.=26) 100-m sprinters; the sample was divided into two subgroups within each sex according to personal best 100-m time: 10.00-10.90 s (M10; N.=22) and 11.00-11.70 s (M11; N.=15) for males and 11.00-11.90 s (F11, N.=14) and 12.00-13.50 s (F12, N.=12) for females. SM was estimated from ultrasound-measured muscle thickness (MT) using prediction equations. RESULTS: There was an approximate 10% difference in 100-m sprint time between sexes, whereas absolute and relative values of SM for female sprinters were 70-71% and 79-84% of the male sprinters, respectively. No differences were observed within each male/female subgroup for fat-free mass, absolute and relative SM, excepting that leg SM index of M10 was higher than M11. The 100-m time was not different (0.27 s, P=0.051) between M11 and F11 subgroups, but absolute and relative values of SM and MT were higher and percent body fat was lower in the M11 than in the F11 subgroup. CONCLUSIONS: Our results suggest that differences in muscle mass may not play a large role in determining successful performance in elite male and female sprinters.